Threats to Saminism Values in the Digitalization Era - Atmaja, Diaz Kusuma; Norkholifah, Yuyun (Program Studi Sosiologi Agama Fakultas Ushuluddin dan Filsafat, Universitas Islam Negeri Ar-Raniry, Banda Aceh, Indonesia, 2024)
This study examines the impact of digitalization on the values of Saminism in the Sikep community of Blora. Saminism, a traditional belief system originating from Java, emphasizes simplicity, non-violence, and harmonious living with nature. However, the digitalization era poses significant challenges to preserving these values. Using a qualitative case study approach, data were collected through in-depth interviews and participatory observations to understand the socio-cultural context in which Samin teachings are practiced. The findings indicate that digitalization has led to a shift in values among Sikep youth, who are increasingly exposed to pop culture and digital technology. This shift has resulted in a decreased understanding and practice of Saminism, as well as a decline in social ethics aligned with its teachings. To address these challenges, the Sikep community must reinforce Saminism teachings and filter foreign cultural influences to align with Sikep values, norms, and traditions. By leveraging digital platforms to promote Saminism teachings, the community can adapt to modern advancements while maintaining their cultural heritage. In conclusion, integrating Saminism principles with modern technology can create a sustainable balance between tradition and progress, ensuring the continued relevance and vitality of Saminism in the digital age.